Analisis Komparatif Hukum Perdata Islam dan Hukum Perdata Indonesia dalam Sistem Hukum Pluralistik di Indonesia - Endang Pujiastuti; Tuti Herawati; Diana Farid; Daud Nurdin (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Indonesia adopts a pluralistic legal system that accommodates various legal traditions, including customary law, civil law inherited from the Dutch Burgerlijk Wetboek, and Islamic civil law. Consequently, the application of civil law is not uniform but depends on judicial competence, the legal status of the parties, and the nature of the dispute. This article aims to examine the similarities, differences, and implementation of Islamic Civil Law and Indonesian Civil Law through a comparative legal approach. This study employs normative legal research using statutory, conceptual, comparative, and case approaches. Data were collected from legislation, court decisions, legal literature, and recent scholarly publications. The findings reveal that Islamic Civil Law emphasizes Sharia principles, maqāṣid al-sharī'ah, and substantive justice, whereas Indonesian Civil Law, derived from the Burgerlijk Wetboek, primarily focuses on legal certainty through contractual freedom and individual rights. Despite their philosophical differences, both legal systems converge in protecting civil rights, ensuring justice, and maintaining legal certainty. Therefore, harmonization between these legal systems is essential to strengthen Indonesia's pluralistic national legal framework.